(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: The foremost goal of orthodontic treatment is to improve dental occlusion and alignment of teeth, which eventually results in a healthy functioning of dentition and facial aesthetics. The aim of the present study was to assess the oral hygiene awareness, difficulties faced and satisfaction level among a group of students undergoing orthodontic therapy during and after treatment. Materials and Methods: A sample of 200 students from Melaka Manipal Medical College, who received orthodontic treatment were included in the study. A cross - sectional study in the form of self-administered questionnaire was carried out. The questions were based mainly to assess the difficulties faced, awareness with regard to oral hygiene and satisfaction level of the participants during and after orthodontic treatment. Results: The difficulties faced by orthodontics patients were in the range of 65 to 85%, which were trouble sleeping, food lodgement and difficulty in maintaining oral hygiene. Study participants were not aware of various cleaning modes though more than 50% used floss. In the post treatment phase, aesthetic appearance was found to be better. Conclusion: The present study showed that the participants who were undergoing orthodontic treatment did not have sufficient knowledge about oral hygiene practices. The participants were satisfied with the aesthetic appearance post treatment.